Experimental Study of the Effect of PH on the Adsorption Capacity of H2S from Waste Water by Using Calcination of Eggshell as an Adsorbent - Habeeb, Omar Abed; K., Ramesh; R. M., Yunus; Ahmad, Mani Malam; Olalere, Olusegun Abayomi (Universiti Malaysia Pahang, 2016)
Many agro-based waste products are found to be very good adsorbents for industrial and domestic wastewater containing hydrogen sulfide. This is due to their lignin and cellulose contents containing structures such as aldehydes, ketones and alcohols as factional groups. This study employs a batch process to investigate the impact of pH on the adsorption capacity of eggshell for the removal of hydrogen sulfide from wastewater. The sample is characterized by using approaches such as SEM, EDX, and particle size distribution test. Thermal analysis is conducted by using Instrument Thermal Analyzer. In the current work, the eggshell is grounded and modified to calcite by using the calcination process. The optimum conditions for the removal of hydrogen sulfide at an initial concentration of 250 mg/L are dosage of 0.1 g/L and agitation speed of 160 rpm. These conditions lead to an adsorption capacity of 21.2 mg H2S.g-1 with an equilibrium time of 400 minutes. The calcination process facilitates the conversion of CaCO3 to CaO. Also, the current study shows that the optimum pH value for effective H2S removal by using eggshell is ~7